Relações biogeográficas de mamíferos na região central da América do Sul - Roman, Cassiano (2009)
The objective of this study was to analyze the influence of climatic and physiographic variables in the geographic distribution of non-flying mammals in a central region of South America. To examine the relationships among areas and endemism of mammals, a priori analysis considering ecoregions and a posteriori analysis based on relationships of 110x110- km squares were performed. Data from non-flying mammals were collected from museums, literature and field observations were considered. Based on that, the occurrence of each species was determined in a grid containing 90 cells, where each square had 1° of latitude and 1° of longitude (110 km x 110 km). Cluster analysis and parsimony analysis of endemicity (PAE) were used to examine the relationships between ecoregions and squares. More than 1500 records were considered and classified in nine orders, 26 families, 86 genus and 139 species of non-flying mammals. Cluster analysis demonstrated four distinguished groups. Classifications based on ecoregions resulted in two main groups of ecoregions, the Eastern and the Western group. Classifications based on cells resulted in the formation of two main groups of ecoregions, the Northern and Southern groups. The richness of mammal species in a central region of South America is under influence of several variables and the geographical distribution of these species was related more with some variables than others. Temperature and topography were the environmental variables that most influenced the mammal species distribution patterns.